AI-POWERED TEACHING MODELS: ENHANCING PEDAGOGICAL STRATEGIES FOR THE 21ST CENTURY CLASSROOM - Geischa Cicilia Mokoagow; Amin Zaki; Faisal Razak (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
The integration of Artificial Intelligence (AI) in education has the potential to transform teaching practices and enhance learning experiences in the 21st-century classroom. AI-powered teaching models, which incorporate personalized learning, adaptive feedback, and intelligent tutoring systems, offer new opportunities to address diverse learning needs and improve educational outcomes. This research investigates the role of AI in enhancing pedagogical strategies by examining its impact on student engagement, academic performance, and teacher efficiency. The study employs a mixed-methods approach, combining quantitative surveys and qualitative case studies across five institutions that have integrated AI tools into their teaching practices. The results indicate that students who engaged with AI-powered tools demonstrated significant improvements in both engagement (82%) and academic performance (75%), particularly through personalized learning features. Educators reported enhanced classroom efficiency, as AI tools helped automate administrative tasks and provided real-time data on student progress. The study concludes that AI-powered teaching models are effective in fostering more personalized, engaging, and efficient learning environments. These models not only support individualized learning but also enhance the broader educational experience by improving communication between students and educators. The research highlights the potential of AI in shaping the future of education and offers practical insights into its integration into pedagogical strategies.